О ГРАММАТИКАЛИЗАЦИИ ГЛАГОЛОВ: (на материале немецкого языка) (Philological Studies, 2019)
The paper examines the questions of grammaticalization of German verbs. Grammaticalization makes actual certain variations of the verb categorical meaning. Grammaticalization is seen as the process of a grammatical sign apperance from a lexical unit and the increase of its grammatical function. The peculiarity of a lexical sign is its autonomy and ability to appear in any linguistic environment. The level of autonomy shows the degree of grammaticalization of lexical signs. The more autonomous a lexical sign is, the lower degree of its grammaticalization, and vice versa. As a result of grammaticalization, the sign loses its autonomy, gains a grammatical meaning and starts performing a grammatical function. In the process of grammaticalization the generalization of the meaning takes place, i.e. the primary lexical meaning of the sign fades away and a general meaning appears. This lets the lexical sign expand its distribution. Grammaticalization is considered to be a continuous process of intensification of a linguistic unit’s grammatization where a “non-grammatical” meaning turns into a grammatical one, and less grammatical becomes more grammatical. The theory of grammaticalization is rapidly developing nowadays, the theory’s object of description is the combination of processes leading to the emergence of grammatical meanings, grammatical categories and grammatical systems.
Keywords: lexical sign, grammatical sign, verb, grammaticalization, categorical meaning, lexical meaning, grammatical meaning, functional and grammatical causative